Manuka honey enhanced sensitivity of HepG2, hepatocellular carcinoma cells, for Doxorubicin and induced apoptosis through inhibition of Wnt/β-catenin and ERK1/2 - Heba R. Al Refaey (Biological Research, 2021)
Abstract Background Recently, there is increasing awareness focused on the identification of naturally occurring anticancer agents derived from natural products. Manuka honey (MH) has been recognized for its biological properties as antimicrobial, antioxidant, and anticancer properties. However, its antiproliferative mechanism in hepatocellular carcinoma is not investigated. The current study focused mainly on investigating the molecular mechanism and synergistic effect of anticancer properties of MH on Doxorubicin (DOX)-mediated apoptotic cell death, using two different p53 statuses (HepG2 and Hep3B) and one non-tumorigenic immortalized liver cell line. Results MH treatment showed a proliferative inhibitory effect on tested cells in a dose-dependent manner with IC50 concentration of (6.92 ± 0.005%) and (18.62 ± 0.07%) for HepG2 and Hep3B cells, respectively, and induced dramatic morphological changes of Hep-G2 cells, which considered as characteristics feature of apoptosis induction after 48 h of treatment. Our results showed that MH or combined treatments induced higher cytotoxicity in p53-wild type, HepG2, than in p53-null, Hep3B, cells. Cytotoxicity was not observed in normal liver cells. Furthermore, the synergistic effect of MH and Dox on apoptosis was evidenced by increased annexin-V-positive cells and Sub-G1 cells in both tested cell lines with a significant increase in the percentage of Hep-G2 cells at late apoptosis as confirmed by the flow cytometric analysis. Consistently, the proteolytic activities of caspase-3 and the degradation of poly (ADP-ribose) polymerase were also higher in the combined treatment which in turn accompanied by significant inhibitory effects of pERK1/2, mTOR, S6K, oncogenic β-catenin, and cyclin D1 after 48 h. In contrast, the MH or combined treatment-induced apoptosis was accompanied by significantly upregulated expression of proapoptotic Bax protein and downregulated expression of anti-apoptotic Bcl-2 protein after 48 h. Conclusions Our data showed a synergistic inhibitory effect of MH on DOX-mediated apoptotic cell death in HCC cells. To our knowledge, the present study provides the first report on the anticancer activity of MH and its combined treatment with DOX on HCC cell lines, introducing MH as a promising natural and nontoxic anticancer compound.